Managing Stakeholder Concerns in Green Building Projects With a View Towards Achieving Social Sustainability: A Bayesian-Network Model - Wen, Shiping; Qiang, Guofeng (Frontiers in Environmental Science, 2022)
Green building projects (GBPs) involve multiple interdependent stakeholders, whose individual and separate concerns have different degrees of impact on sustainability management. These concerns are highly complex, subject to many uncertainties, and pose significant challenges to decision-makers during sustainability assessments, especially with regard to the social aspects of the project. As such, addressing the complexity of stakeholder concerns and optimizing the decision-making process in green building projects from the stakeholder perspective are crucial to improving practices in social sustainability management. However, to date, there is a lack of relevant empirical studies on this subject. This study proposes a decision-making model based on Bayesian networks (BN); a project network decision model is also constructed from a social sustainability perspective. A diagnostic analysis and sensitivity analysis of the constructed model identify the key stakeholder concerns that affect the social sustainability of the project. To verify its feasibility, the BN model is applied to a green building project, specifically, the Wuhan International Commerce Center, China. The results identify green design and construction, an abundance and stability of project funds, and conveniently-situated service facilities as the primary, sensitive stakeholder concerns that significantly impact social sustainability. The findings show that the BN model can be used as a long-term management decision-making tool for this project. The uncertainty problem associated with changes in sustainability levels induced by the multiplicity of stakeholders is addressed in this study. Furthermore, the findings expand the topic of social sustainability in green construction projects. These findings aid project decision-makers in managing stakeholders individually based on their various concerns, as well as improving the social sustainability of green building projects.